Floatable graphitic carbon nitride/alginate beads for the photodegradation of organic pollutants under solar light irradiation. (15th October 2022) - Falletta, Ermelinda; Longhi, Mariangela; Di Michele, Alessandro; Boffito, Daria C.; Bianchi, Claudia L.
Abstract: Graphitic carbon nitride, both as powder and alginate floating beads, was synthesized by an easy and cheap approach using two different precursors (melamine and urea) and properly characterized by several techniques. The effect of the type of precursor on the photoactive properties of the final materials was investigated. Their activity towards the photodegradation of different pollutants (dyes, drugs, and herbicides) both in ultrapure water and simulated drinking water under solar light irradiation was investigated, reaching extraordinarily high photodegradation results (99% for diclofenac and rhodamine B and 90% for isoproturon) compared to the literature. The floating photocatalysts showed good stability during recycling maintaining high performances after 5-time usage without post-treatment. Finally, liquid chromatography equipped with mass spectrometry (UPLC/MS) was used to identify the main by-products formed during the photodegradation tests, and a plausible transformation pathway has been proposed. Graphical abstract: Image 1 Highlights: g-C3 N4 /calcium alginate floating beads were prepared. g-C3 N4 /calcium alginate floating are cheap and reusable materials for efficient organic pollutants' photodegradation. Tests in simulated drinking water show high performance for the floating photocatalysts. Floating photocatalysts show a high photodegradation efficiency retention up to five runs. Reaction intermediates are identified.